Productivity, grain yield and physical attributes in different cropping systems with common bean planting (Research, Society and Development, 2022)
The bean crop belongs to the fabaceae family, being a very important legume for the incorporation of newly installed areas. The objective of this work was to test a variety of common bean (Phaseolus vulgaris L.) in two cropping systems, conventional tillage system and no-tillage system in the Campos Gerais Region - Paraná. An experiment was carried out in a Red Latosol under no-tillage and conventional tillage. To evaluate the agronomic performance, the bean crop with the variety BRS Esteio was used. At harvest maturity, the total yield of each useful plot was evaluated, converted into kg/ha. As well as the mass of 1000 seeds, number of grains per plant, number of pods per plant, diameter and height of plants. For the physical attributes, soil density and total organic carbon were evaluated. For the agronomic variables, it was observed that the no-tillage system was more effective in relation to the conventional planting system. For the physical attributes of the soil there was no statistical difference. It is concluded that the no-tillage system provides an increase in pod yield and productivity. As it is a newly installed area, a longer period is needed to assess the advantages of the no-tillage system in terms of soil attributes.